The Nazi Olympics Berlin 1936
Informationsseite (online Ausstellung) zu den politischen Zielen, die die Nazis mit der Durchführung der Olympischen Spiele 1936 in Berlin verbanden und den verschiedenen Maßnahmen, die damit im Zusammenhang standen: I N T R O D U C T I O N G E R M A N Y Nationalism - Police State - Racism - Antisemitism S P O R T S Race Hygiene - Regimentation - Sport as Military Training - Indoctrination of Youth - Nazi Control of Olympics - Exclusion of Jews - Persecution of Athletes B OY C O T T The Debate - African American Responses - "Jim Crow" America - Louis-Schmeling Fight - American Jewish Responses - American Antisemitism - American Jewish Boycotters - World Responses TO BERLIN THE OLYMPICS Preparations - Winter Games - Remilitarization - Nazi Propaganda - Facade of Hospitality - Opening of the Games - Athletic Competition - African American Athletes - Jewish Athletes THE AFTERMATH Persecution - War - The Holocaust